?rea de cobertura em ambiente de propaga??o modelado com a distribui??o n-? - Figueiredo, Denilson de Oliveira (2004)
This dissertation develops the equations for the calculation of the coverage area in an environment modeled according to the n-? distribution considering only the variations due to the short-term and non-selective frequency fading. The n-? distribution is a generic approach to signal propagation in nonhomogeneous media and encompasses the Rayleigh and Nakagami-m distributions as special cases. As a first contribution one has to calculate the coverage of the sites at a distance x - this approach estimates the fraction of the locations on an x-ray circumference where the mobile receives an instantaneous power greater than a certain threshold. The second contribution is the calculation of the coverage of the locations up to a distance x - estimates the fraction of the area of ??the circle with x-ray where the instantaneous power of the received signal is greater than a certain threshold. It has been shown that the equations for the coverage areas for the environments modeled with the Nakagami-m and Rayleigh distributions can be obtained from the equations for the n-? distribution.